摘要策略教學對提升國小五年級學童摘要能力與閱讀理解的成效 Examining the Effects of Summarization Strategy Instruction on Summary Skills and Reading Comprehension of Fifth Graders - 陸怡琮 I-Chung Lu (National Taiwan Normal University, 2011)
本研究主要目的在設計適用於國小高年級國語科的摘要策略教學模式，並檢視此模式對提升學生摘要能力和閱讀理解之效果。研究設計採控制組前後測的準實驗設計，以屏東縣2所國小各兩班五年級學生為對象，隨機分配每校中的一班為實驗組，接受融入國語科的摘要策略教學，另一班為控制組，進行國語評量卷的習寫與回饋。教學前、後及教學結束後1 個月，進行摘要能力和閱讀理解的測量，實驗組學生在教學結束後填答回饋問卷。結果顯示，摘要策略教學對提升摘要能力有立即與維持的效果，且在追蹤後測階段對低能力學生摘要表現的促進效果大於對高能力學生，但對促進閱讀理解則無顯著效果，學生對摘要策略與教學都有非常正向的態度。 This study designed a summarization strategy instruction for elementary students and examined its effects on the summary skills and reading comprehension of fifth graders. Four fifth-grade classes from two elementary schools in Pingtung County participated in the study. Using a quasi-experimental pretest-posttest control group design, one class in each school was assigned to the experimental group, which received the summarization strategy instruction, while the other class in each school served as the control group, which took practice tests on language arts and received feedback from the teacher. Before, immediately after, and four weeks following the experiment, both groups were tested on summary skills and reading comprehension. The experimental group also filled out a questionnaire after the experiment on their perceptions of the instruction. The results indicated that the experimental group scored significantly higher than the control group did in summary skills in both the posttest and delayed posttest and interaction effect was found between instruction and reading ability in the delayed posttest. The two instruction groups did not differ in reading comprehension after the experiment. Students in the experimental group were positive toward the strategy and the instruction.